Highly selective electrochemical reduction of CO2 to formate on metal-free nitrogen-doped PC61BM. Issue 24 (1st June 2018) - Chen, Zhipeng; Mou, Kaiwen; Yao, Shunyu; Liu, Licheng
Abstract : Herein we report the first example of a nitrogen-doped fullerene derivative for the electrochemical reduction of CO2 to formate with a high faradaic efficiency. Abstract : Herein we report the first example of a nitrogen-doped fullerene derivative metal-free catalyst for electrochemical reduction of CO2 to formate. The N-doped PC61BM ([6, 6]-phenyl-C61-butyric acid methyl ester) (N-C61) exhibits an excellent activity toward CO2 reduction, reaching a high faradaic efficiency (FE) of 91.2% for formate production with good stability at a moderate overpotential of 700 mV. A partial formate current density ( j HCOO − ) of 14.7 mA cm −2 was observed at −1.1 V ( vs. RHE), which is larger than those of most metal-free electrocatalysts. Additionally, a detailed study suggests that graphitic N-defects are the most likely active sites for formate formation. This work provides a practical and feasible way to fabricate an N-doped fullerene derivative and other heteroatom doped fullerene-based electrocatalysts for electrochemical reduction of CO2 .